The effects of personalized learning courseware (PLaCE) and the tracking of ESL learners activities (TLA) in blended learning / Aini Faridah Azizul Hassan - Azizul Hassan, Aini Faridah (2021)
The concern over low literacy attainment in English language among Malaysian learners has caused great concern among many educators. In today's world that demands choice, opportunities, and more individualized solutions, a one size fits all model is no longer capable to fulfill all public education learners needs effectively. A more personalized learning courseware is a model that can serve as a paradigm shift to our existing classroom-based model, traditional teaching and learning practices. The purpose of this study is to explore ways to enhance UiTM English language learners via face-to-face and blended mode through the use of Personalized Learning Courseware (PLaCE). PLaCE was developed to integrate the learners’ skills in using grammatically correct structures in academic context. This study also tracks learners’ acceptance, learning styles, and learning activities in a 14-week course. A mixed method (quantitative and qualitative approaches) is employed in this study. The quantitative research is conducted through experimental research (pretest-posttest two group designs). Qualitative data is used to triangulate and to get an indepth understanding of learners’ satisfaction and dissatisfaction of their learning via journal writing. The learners were randomly assigned into the experimental class and controlled class. For the experimental class, learners were given PLaCE whereas in the controlled class PLaCE was not given. The result of this study showed that the learner’s performance improved while they were engaging in PLaCE. Next, it was found that all experimental learners’ acceptance towards the use of technology were positive. In addition, the findings on the learners learning styles found that the visual style was the most dominant style possessed by the learners. Finally, the outcomes on full-time and e-PJJ learning activities showed similar results for both mode of learners. Participants of this study expressed that language learning materials using multimedia were very entertaining, informative and beneficial for their English study. They evaluated their English learning experience through the use of PLaCE as effective and motivating. In this study, it revealed that using PLaCE could be served as motivating factors to improve learners’ grammar competence as well as to boost their English language learning attitude, cater for different learning styles and enhance learners autonomous learning experience.